Pedagogical Competence of Elementary School Teachers: Basic Knowledge and Forms of Learning Activity - Hanum, Citra Bahadur; Robandi, Babang (Mimbar Sekolah Dasar, 2023)
A 2019 survey by the Programme for International Student Assessment (PISA) showed that Indonesia occupied a low position, specifically 74th out of 79 countries. In line with this problem, the government has accommodated teachers by implementing the Teacher Competency Test (TCT) since 2012 specifically for teachers who would take part in certification. The focus of TCT is to identify teacher weaknesses in mastering pedagogical and professional competencies. This research aims to explore and analyze the methods of elementary school teachers as fresh graduates at one university in West Java in actualizing pedagogical competence. Mixed method was used to obtain quantitative and qualitative data. This study used two sampling techniques, random sampling to obtain quantitative data and purposive sampling for qualitative data. The instruments used were questionnaires and interviews. The data analysis referred to the sequential explanatory research design. The findings showed various elements of the four indicators of teacher pedagogical competence beginning knowledge foundation, the lesson planning steps determined by the teacher, the teacher's creative pedagogic manifestations, and the teacher's manifestation as a student facilitator. The various intensities and forms of activities were found in the research results. Further outlook of the findings can become a bridge between teachers and students. Students' understanding of the material can be more comprehensive and more creative. It can lead to finding out students' problems and obstacles so that they can decide on solutions quicker and more comprehensively.